Burn injuries in rural India: a comprehensive review of epidemiology, risk factors and preventive strategies - Sahu, Ranjit K.; Nayak, Abhisek; Jena, Harapriya; Sahu, Sachidananda; Aisureya, J. B.; Saha, Sanjana; Barik, Umesh; Pati, Hemalata; Sahu, Sabita (International Journal Of Community Medicine And Public Health, 2025)
In India, burns rank as the second leading cause of unintentional injuries. Few studies have examined the trend of burn injuries in rural India. Managing burn injuries poses a significant challenge in the country, which has the highest rate of female fatalities worldwide from flame burns. Burns can occur anywhere; however, they are more prevalent in rural areas, impacting the impoverished. The most frequent type is flame burns, with kerosene and flammable clothing worn by women being the factors involved. The healthcare network’s infrastructure is strong, but there is a significant shortage of resources. To achieve a positive transformation, it will be necessary to have more qualified individuals ready to serve in the rural regions. In many instances, burn patients face mistreatment in the community before reaching the healthcare facility. The community holds misconceptions about burn management that hinder effective management within the facility. On the other hand, the facility’s preparedness poses a significant challenge. To maintain quality and consistency in burn care in rural India, it is essential to foster knowledge and awareness within the community regarding burn prevention and their involvement. In this way, timely availability of facilities will enhance community confidence, consequently saving thousands of lives from burn injuries in rural India.